2016
DOI: 10.1653/024.099.sp107
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of X-Rays on Cytological Traits ofTuta absoluta(Lepidoptera: Gelechiidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 74 publications
2
7
0
Order By: Relevance
“…In T. absoluta , Carabajal Paladino et al. (2016) determined the haploid chromosome number of n = 29 and identified the largest elements as sex chromosomes morphometrically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In T. absoluta , Carabajal Paladino et al. (2016) determined the haploid chromosome number of n = 29 and identified the largest elements as sex chromosomes morphometrically.…”
Section: Resultsmentioning
confidence: 99%
“…Similar large chromosome pairs were also observed in representatives of the families Pyralidae, Oecophoridae, and Gelechiidae with reduced chromosome numbers, but were considered autosomal fusion products (Ennis 1976). Carabajal Paladino et al. (2016), however, showed that the large chromosome pair corresponds to sex chromosomes in an invasive gelechiid pest, the tomato leafminer Tuta absoluta (Gelechiidae).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies examined only male metaphase I chromosomes, in which light microscopy lacks resolution to identify types of aberrations. A recent study, examining mitotic metaphases and pachytene spermatocytes alongside metaphase I in F 1 males of the tomato leafminer, Tuta absoluta (Meyrick), reported that the irradiation of male parents with a substerilizing dose of 200 Gy induced mainly chromosomal translocations and fragmentation of the chromosomes [69]. However, the most valuable results were obtained using a modified microspreading technique for electron microscopy to study radiation-induced chromosome aberrations in F 1 females and males of the flour moth [63].…”
Section: Inherited Sterility In Lepidopteramentioning
confidence: 99%
“…The above detailed analysis of radiation-induced chromosomal aberrations by electron microscopy [63] also offered an explanation of the higher IS found in F 1 males than in F 1 females, as reported in previous studies [11]. Three factors might contribute to this phenomenon: (i) the ability of males to survive more extensive damage to chromosomes than females, (ii) the occurrence of crossing-over during spermatogenesis, which might increase the number of unbalanced gametes produced by F 1 males but not in the achiasmatic meiosis of females, and (iii) a higher impact of radiation-induced deleterious effects on the fertility of F 1 males, such as defects in spermiogenesis or sperm transfer [69,71].…”
Section: Inherited Sterility In Lepidopteramentioning
confidence: 99%
“…The use of inherent or enhanced resistance in plants, such as resistant host plant cultivars (Cherif et al 2019), botanical extracts (Soares et al 2019), transgenic resistant plants (Selale et al 2017) and enhanced plant resistance via manipulation of soil abiotic factors (e.g., bottom-up effects) (Blazheyski et al 2018;Han et al 2019b), is another promising management strategy for reducing damage by this pest. Novel management technologies, such as RNA interference (RNAi) (Majidiani et al 2019) and sterile insect technique (SIT) (Cagnotti et al 2012(Cagnotti et al , 2016Paladino et al 2016), have been explored recently, which could be considered in the further management of T. absoluta.…”
Section: Discussionmentioning
confidence: 99%